New approaches to ranking economics journals - Yolanda K. Kodrzycki; Pingkang David Yu (Federal Reserve Bank of Boston, 2005)
This study develops a flexible, citations-adjusted ranking technique that allows a specified set of journals to be evaluated using a wide range of alternative criteria. As a result, the set of evaluated journals is not constrained to be identical to the set of evaluating journals. We also draw a critical distinction between the influence of a journal and the influence of a journal article, with the latter concept arguably being more relevant for potential contributors and those who evaluate research productivity. The list of top economics journals changes noticeably when one examines citations in the social science and policy literatures, and when one measures citations, either within or outside economics, on a per-article basis rather than in total. The changes in rankings are due to the relatively broad interest in applied microeconomics and economic development, to differences in the relative importance that different literatures assign to theoretical and empirical contributions, and to the lack of a systematic effect of journal size on average influence per article. As a related observation on interdisciplinary communications, we confirm other researchers' conclusions that economics is more self-contained than almost any other social science discipline, while finding, nevertheless, that economics draws knowledge from a range of other disciplines.
Keywords: A10; A12; 330; economics journals; social sciences journals; policy journals; rankings; citations; research productivity; interdisciplinary communications; Publikationsanalyse; Wirtschaftswissenschaft; Fachzeitschrift; Ranking-Verfahren